Pengaruh Transparansi, Akuntabilitas Dan Partisipasi Terhadap Pengelolaan Keuangan Kelurahan Di Kecamatan Kartoharjo Kota Madiun - Wahyuningtyas Mutiara Putri; Rusbiyanti Sripeni; Andri Hasmoro Kusumo Broto (Universitas Merdeka Madiun, 2020)
Abstractâ€” This study aims to find out how far the implementation of transparency, accountability and participation of village finance management in Kartoharjo Subdistrict Madiun City.The research method used is qualitative method with descriptive approach. Respondents in this research are 52 kelurahan in manguharjo urban village. Data collection techniques used in the form of interviews, observations and questionnaires. Data obtained from the primary data by using questionnaires, data analysis techniques using multiple linear regression analysis with SPSS software program version 23.00 for windows and hypothesis testing is done by using the F test. The results of this study indicate that transparency posistif influence on village financial management, while accountability and participation have no effect on the management of village finance.Â Keywordsâ€”: Kelurahan Financial Management; Transparency; Accountability; Participatio.